Ekranisasi Novel Lust, Caution Karya Eileen Chang dan Film Lust, Caution Karya Ang Lee - Garcia Paulus, Avelina; Arifin, Yohan Yusuf (Universitas Al Azhar Indonesia, 2025)
Adaptation from novel to film has become one of the most striking trends in the entertainment industry, so that many films can be found that are sourced from novels, one of which is the film Lust, Caution. This study discusses the ecranization of the novel and film Lust, Caution by Eileen Chang and directed by Ang Lee which aims to analyze the differences in the storyline, characters, and time and place settings contained in the novel and film Lust, Caution such as the possibility of shrinking, adding and varying changes that occur. The research method used is the descriptive analysis method. The data collection techniques used are the observation and note-taking techniques and literature studies. The data sources used are the English version of the novel Lust, Caution by Eileen Chang and the film Lust, Caution directed by Ang Lee. The results of the study show that the ecranization process occurs because of differences in imagination between the novelist and the director, as well as the adjustment of the two work mediums from words to moving images. Even so, this ecranization process does not change the outline of the story. The ecranization in this film also shows changes between the content of the novel and the content of the film, this was done to provide a new interpretation of the original work.Keywords – Ecranzation, Film, Lust Caution, Novel.